Leadership : perspectives from the front line - Veldsman, Theo H.; Johnson, Andrew J. (Andrew Joseph); Madonsela, Thuli (KR Publishing, 2016)
Two internationally recognised thought leaders on leadership teamed up with over 80 contributors to produce the most comprehensive and "biggest" business leadership book ever published in South Africa. With 89 contributors, 56 chapters, 1000+ pages and featuring a foreword from Advocate Thuli Madonsela in hard cover, the book addresses Leadership from every possible angle. This is the most comprehensive book on leadership ever published in South Africa. It provides cutting-edge thinking about leadership. It synthesises the latest insights from SA's top leaders and experts on leadership - offering readers practical tools they can implement immediately -- Publisher's description.